2018
DOI: 10.7759/cureus.2288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Perioperative Outcomes in Minimally Invasive Oblique Lateral Lumbar Interbody Fusion versus Open Fusions: A Multivariant Analysis

Abstract: BackgroundObesity is an increasing public health concern associated with increased perioperative complications and expense in lumbar spine fusions. While open and mini-open fusions such as transforaminal lumbar interbody fusion (TLIF) and minimally invasive TLIF (MIS-TLIF) are more challenging in obese patients, new MIS procedures like oblique lateral lumbar interbody fusion (OLLIF) may improve perioperative outcomes in obese patients relative to TLIF and MIS-TLIF.PurposeThe purpose of this study is to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Obesity is a significant factor in the initial clinical and radiological findings associated with lumbar spine disease [9]. Although there have been reports regarding the effects of obesity on surgical outcome [10-14], no study on TLIF procedure has compared the peri-operative data of patients with BMI < 30 kg/m 2 to peri-operative data of patients with BMI 30–39 kg/m 2 . TLIF surgery has been performed for many years and is a generally accepted procedure [6].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a significant factor in the initial clinical and radiological findings associated with lumbar spine disease [9]. Although there have been reports regarding the effects of obesity on surgical outcome [10-14], no study on TLIF procedure has compared the peri-operative data of patients with BMI < 30 kg/m 2 to peri-operative data of patients with BMI 30–39 kg/m 2 . TLIF surgery has been performed for many years and is a generally accepted procedure [6].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the NOS (supplementary file; Table S2 ), the non-randomized controlled trials involved in this study were considered to be of high quality (5–9 points). 36 Two studies 32 , 35 received 8/9, two studies 31 , 34 received 7/9, and the last study 33 received 6/9 (supplementary file; #2). In addition, the GRADE standard quality classification principle showed that low back pain VAS score, ODI index score, and complication rate were medium-quality evidence.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Abbasi and Grant demonstrated that obesity was associated with increased surgical time and blood loss in transforaminal lumbar interbody fusion but not in OLIF. 16 A review by Goyal et al analyzed 32 studies (23,415 lumbar spine surgery patients), and they found that obese patients undergoing open spine surgery had higher blood loss, longer operative times, and higher reoperation rates than nonobese patients. However, while they did not find a difference in operative times and blood loss between obese and nonobese patients undergoing minimally invasive spine surgery, they did find that obese patients had longer operative times for MIS.…”
Section: Discussionmentioning
confidence: 99%